2018
DOI: 10.1002/jmri.26541
|View full text |Cite
|
Sign up to set email alerts
|

Role of proton MR spectroscopy in the differentiation of borderline from malignant epithelial ovarian tumors: A preliminary study

Abstract: Background Due to the overlapping imaging appearances between borderline and malignant epithelial ovarian tumors (EOTs), borderline EOTs often represent a diagnostic challenge on conventional MRI. Proton magnetic resonance spectroscopy (1H‐MRS) might have potential to differentiate borderline from malignant tumors. Purpose To investigate the ability of 1H‐MRS to differentiate borderline from malignant EOTs. Study Type Prospective. Population In all, 278 patients with adnexal masses. Field Strength/Sequence 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In a traditional MRI reading session, the imaging signs always overlap with each other to some extent (for example, large size, solid components, irregular and thick septa) and lead to an inaccurate diagnosis (27,(30)(31)(32). A recent study with proton MRS reported that the SEN and SPE were 91% and 100% for solid components, respectively; additionally, the SEN and SPE were 84% and 82% for cystic components, respectively (12). However, MRS scans are highly unit-dependent and time-consuming examinations and require operators with more experience than conventional methods do.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a traditional MRI reading session, the imaging signs always overlap with each other to some extent (for example, large size, solid components, irregular and thick septa) and lead to an inaccurate diagnosis (27,(30)(31)(32). A recent study with proton MRS reported that the SEN and SPE were 91% and 100% for solid components, respectively; additionally, the SEN and SPE were 84% and 82% for cystic components, respectively (12). However, MRS scans are highly unit-dependent and time-consuming examinations and require operators with more experience than conventional methods do.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has high diagnostic performance in differentiating between ovarian benign tumors and malignant tumors (5)(6)(7)(8)(9). Considering the ability to discriminate BOTs from malignant epithelial ovarian tumors, conventional MRI varies with a sensitivity of 58-100% and a speci city of 61-100%, respectively (7,(10)(11)(12)(13). Functional MRI scans (dynamic contrast-enhanced MRI, diffusion-weighted imaging(DWI), MR spectroscopy(MRS), etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a traditional MRI reading session, the imaging signs always overlap with each other to some extent (for example, large size, solid components, irregular and thick septa) and lead to an inaccurate diagnosis (27,(30)(31)(32). A recent study with proton MRS reported that the SEN and SPE were 91% and 100% for solid components, respectively; additionally, the SEN and SPE were 84% and 82% for cystic components, respectively (12). However, MRS scans are highly unit-dependent and time-consuming examinations and require operators with more experience than conventional methods do.…”
Section: Discussionmentioning
confidence: 99%
“…This 'data-driven' approach which enables the extraction of innumerable quantitative features from tomographic images has already shown promising results in the classification of ovarian epithelial cancer, as well as in predicting several outcome measures [56,57]. MR spectroscopy has also been reported to play a role in differentiating between borderline and malignant epithelial ovarian tumours [58]. However, epithelial tumours are rare in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%